Spying on Democracy : Government Surveillance, Corporate Power and Public Resistance - Boghosian, Heidi (Open Media book., 2013)
"Personal information contained in your emails, phone calls, GPS movements and social media is a hot commodity, and corporations are cashing in by mining and selling the data they collect about our private lives. "Spying on Democracy" reveals how the government acquires and uses such information to target those individuals and/or groups it deems threatening"--